Clinical mitochondrial medicine - Chinnery, Patrick F.; Keogh, Michael J. (Cambridge University Press, 2018)
Mitochondrial disorders are a highly diverse group of conditions that can affect almost every major system in the human body, often mimicking common disorders. This clinical variety often results in prolonged and often dangerous, diagnostic delays. This textbook provides a practical framework, to enable rapid identification, investigation, and treatment of mitochondrial disorders across the spectrum of clinical practice. Clinically relevant and comprehensive, this textbook employs a system- and case-based approach for practitioners of all levels. It focuses on major phenotypic features, syndromes and management relevant for clinical practice, within a broad overview of the field. This interactive book supports readers with knowledge distilled from over 20 internationally recognized, mitochondrial experts
Title from publisher's bibliographic system (viewed on 27 Apr 2018)
Machine generated contents note: Part I. Introduction to Mitochondrial Medicine: 1. Mitochondria in health and disease Carlo Viscomi and Massimo Zeviani; 2. Clinical approach in children Shamima Rahman; 3. Clinical approach in adults Michael J. Keogh, Hannah E. Steele and Patrick F. Chinnery; 4. Laboratory investigation of mitochondrial diseases Robert W. Taylor and David R. Thorburn; 5. Clinical genetics of mitochondrial diseases Marni J. Falk and Colleen Clarke Muraresku; 6. Clinical management of mitochondrial diseases Rita Horvath; Part II. Systems Involved in Mitochondrial Diseases: 7. Neurology -- the central nervous system Michael J. Keogh, Hannah E. Steele and Patrick F. Chinnery; 8. Neurology -- the peripheral nervous system -- muscle and nerve Robert D.S. Pitceathly, Michael G. Hanna and Mary M. Reilly; 9. Ophthalmology Patrick Yu-Wai-Man, Chiara La Morgia and Valerio Carelli; 10. Audiology Peter Kullar; 11. Cardiovascular medicine Michael J. Keogh, Hannah E. Steele and Patrick F. Chinnery; 12. Respiratory medicine and anaesthesiology Michael J. Keogh, Hannah E. Steele and Patrick F. Chinnery; 12. Respiratory medicine and anaesthesiology Philip G. Morgan and Margaret M. Sedensky; 13. Endocrinology and diabetes Mark Walker, Alison J. Heggie, Andrew M. Schaefer and Grainne S. Gorman; 14. Gastroenterology and hepatology Irenaeus F.M. de Coo and Jessie M. Hulst; 15. Nephrology Thomas M.F. Connor and Patrick H. Maxwell; 16. Psychiatry Laurence A. Bindoff
Keywords: Mitochondrial pathology